The Effect of Storytelling Activities on the Language Skills of 5-6 Year Old Children at Bhakti Famili Kindergarten, Bengkulu - antika, rini; Nirwana, Evi selva (International Journal of Education, Information Technology, and Others, 2025)
This study aims to determine the effect of storytelling activities on the language skills of children aged 5-6 years at Bhakti Famili Kindergarten Bengkulu. This study is a quantitative study with an experimental method. This study was conducted by giving treatment to children in the experimental class. The number of samples in this study was 10 children, with a sampling technique where the samples taken were samples that represented the existing population. Data collection techniques were carried out by observation, documentation and questionnaire statements. The existing questionnaire statement data were analyzed using the SPSS program. The existing data were tested with the Paired Sample T Test. The results of the study showed that there was an effect of storytelling activities on language skills in children aged 5-6 years, this was evidenced by the results of the Sig test value (2 tailed) 0.001 <0.05. Children's language skills increased after storytelling activities were carried out in the experimental class, while in the control class the increase was very minimal. This was evidenced by the mean value of the experimental class 74 while in the control class it was 43.6. This condition proves that the influence of children's language abilities increases when storytelling activities are given to children aged 5-6 years at Bhakti Famili Kindergarten, Bengkulu